PTU-267 Training in gastroenterology in severn: implementation of change improves training. (28th May 2012) - Chelvaratnam, U; Arthurs, E; Mehta, T; Pugh, S; Lockett, M
Abstract : Introduction: Feedback on training posts is collected by a variety of different bodies. The Quality Panel was developed to review the quality of gastroenterology training in the region. Feedback on training posts was found to be of variable quality, incomplete, and difficult to analyse. The aim was to create a specific, reproducible method of assessing gastroenterology and general internal medicine (GIM) training, to provide feedback on individual posts and facilitate improvements in training. In 2010 we conducted a survey of training within the region which identified specific areas for improvement which were fed back to individual trusts. This survey was repeated in 2011 to assess for changes. Methods: The 2010 survey comprised of 55 questions within seven domains of gastroenterology and GIM training. Questions were determined based on previous surveys and areas of importance according to consultant and trainee opinion. It was emailed to all registrars in the Severn deanery. Data were collected for the last 3 years of training (2007–2010); preserving anonymity and eliminating bias. Answers correlated to numerical scores, with high scores correlating with high quality. Mean scores were calculated per domain, per trust; a total score was then calculated. The data were presented to the Quality Panel and training committee. Individualised feedback was given to each trust. The survey was repeated in 2011 (with 18 additional questions) to monitor improvements and was analysed with data from 2008 to 2010. Results: The 2010 survey included 37 anonymised responses from 21 trainees at nine hospitals within the Severn region. Responses by trust varied from 3 to 9. Mean overall numerical score was 26.1 (range 24.4–28.6). All trusts scored lowest in providing GIM training with a mean score of 3.1 (range 2.7–3.6); educational support scored highest with a mean score of 4.4 (range 3.4–4.8). The 2011 survey included 46 anonymised responses from 21 trainees at nine hospitals. Responses by trust varied from 3 to 8. Mean overall numerical score was 26.8 (range 24.7–28.7) and 34.2 (range 31–36.8) with the additional questions. All trusts either improved or retained the same score. All trusts scored lowest in providing GIM training with a mean score of 3.3 (range 2.9–3.8); educational support scored highest with a mean score of 4.5 (range 4–4.8). Conclusion: Creation of a new survey achieved a good response rate and generated speciality specific outcomes and relevant data. This method of assessing training facilitates informed feedback to trusts. Repetition of the survey has shown that feedback-led implementation of change has improved training in Severn. By collecting data on 3 years of training, improvements may have been underestimated. The methodology is reproducible and may benefit training in other specialities. Competing interests: None declared.